2022
DOI: 10.1108/imefm-11-2020-0569
|View full text |Cite
|
Sign up to set email alerts
|

Determining intention to choose Islamic financial products using the attitude–social influence–self-efficacy (ASE) model: the case of Turkey

Abstract: Purpose This study aims to analyze the effects of attitude, social influence and self-efficacy on the behavior of using Islamic financial products based on the attitude–social influence–self-efficacy (ASE) model. Design/methodology/approach In view of the research objective, an explanatory research design was used in this study. In the study, because a conceptual assessment was not made, or a proposal was not developed, the ASE model was used. In testing the ASE model, the structural equation modeling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Customer attitude also helps with financial risk management, insurance, and investment planning [32]. Saygili et al [33] found the relationship between Islamic financial literacy and customer attitude towards Islamic banking products and services in Turkey. As a result, the study postulated: Hypothesis 1 (H1).…”
Section: Literacy On Islamic Financementioning
confidence: 99%
“…Customer attitude also helps with financial risk management, insurance, and investment planning [32]. Saygili et al [33] found the relationship between Islamic financial literacy and customer attitude towards Islamic banking products and services in Turkey. As a result, the study postulated: Hypothesis 1 (H1).…”
Section: Literacy On Islamic Financementioning
confidence: 99%
“…The variable "social influence" which is one of the main variables of the ASE model in this study has been the topic of several studies conducted based on Islamic financial products, and researchers have found a statistically significant effect on intentions to use Islamic finance (Abourrig, 2021;Atal. et al, 2022;Dzuljastri Abdul Razak and Muhamad Abduh, 2012b;Mindra et al, 2022;Mukti et al, 2022b;Saygılı et al, 2022b). Therefore, in this study, it was expected that consumers' intentions to use sharia cooperatives will be influenced by social influences.…”
Section: H1 Islamic Financial Literacy Has a Significant Positive Eff...mentioning
confidence: 84%
“…However, not too many studies use the ASE model as a test of the perspective of Islamic financial products. The study of determining factors for choosing Islamic financial products stated that the variables of attitude, social influence and selfefficacy had a statistically significant effect on consumer intentions to use Islamic financial products (Saygılı et al, 2022b). Another study also showed the ASE model as a variable that affects the utilization of Islamic banks in Indonesia (Nugroho et al, 2017b).…”
Section: Ase Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Rahayu et al, 2017;Saygılı et al, 2022) examining the positive effect of social influence on repurchase suggest that social influence affects repurchase intention. Hutahaean et al (2020) also describe that social influence has a significant effect on purchase intention.…”
Section: Hypothesis Developmentmentioning
confidence: 96%